NEIGHBOURHOOD AND SOCIAL INFLUENCES ON PARTICIPATION IN EVERYDAY ACTIVITIES AMONG OLDER ADULTS WITH CHRONIC HEALTH CONDITIONS - Hand, Carri (My University, 2011)
Older adults with chronic health conditions experience limitations participating in everyday activities. Neighbourhood characteristics and social support can offset individual impairments and help to facilitate participation; however, gaps in this literature exist. This thesis presents the results of three studies that explore the influence of neighbourhood and social factors on participation in everyday activities among older adults with chronic health conditions. The first paper describes a scoping review of academic literature regarding neighbourhood influences on participation. The findings of the review indicated that neighbourhood economic status, amenities, problems, mobility barriers, cohesion, and safety may influence participation but the pathways through which this occurs are not clear.
The second paper uses findings from a cross-sectional survey (n=248) that examined the relationship between perceptions of neighbourhood characteristics and satisfaction with participation among older adults with chronic health conditions. Path analysis showed that fewer neighbourhood problems directly predict higher participation while higher neighbourhood cohesion and safety indirectly predict higher participation.
The third paper uses data from the same cross-sectional survey to examine the types of social support that most strongly predict satisfaction with participation. Regression analyses showed that participants who perceived greater tangible support and positive social interaction support had more satisfaction with participation than participants with lower levels of these types of support.
The findings in this thesis extend previous research by showing that neighbourhood characteristics influence participation even after accounting for social and individual factors. This research identified a potential pathway from neighbourhood characteristics to participation that includes neighbourhood cohesion and social support and established a link between positive social interaction support and participation. The findings in this thesis help to better understand neighbourhood and social influences on participation. These influences may be addressed through clinical or policy interventions to facilitate participation in older adults with chronic health conditions.
Keywords: older adults; chronic disease; human activities; residence characteristics; social environment; Medicine and Health Sciences; Medicine and Health Sciences